Inflammatory pseudotumor of the spleen concomitant with renal cell carcinoma: case report - Ioshii, Sérgio Ossamu (2004)
CONTEXT: Inflammatory pseudotumor is a rare benign lesion that can occur at a wide variety of primary sites. It is usually worrisome for the patient and the medical staff, since it cannot be clinically or radiologically distinguished from malignant entities. CASE REPORT: We report on a case of splenic inflammatory pseudotumor presenting with concomitant renal cell carcinoma. Despite the alarming macroscopic appearance of pseudotumors, their microscopic features usually confirm the inflammatory nature of such lesions. Evidence regarding the etiology of pseudotumors is still lacking, but hypotheses have been created.